What is the prevalence of developmental prosopagnosia? An empirical assessment of different diagnostic cutoffs. (April 2023) - DeGutis, Joseph; Bahierathan, Kanisha; Barahona, Katherine; Lee, EunMyoung; Evans, Travis C.; Shin, Hye Min; Mishra, Maruti; Likitlersuang, Jirapat; Wilmer, Jeremy B.
Abstract: The prevalence of developmental prosopagnosia (DP), lifelong face recognition deficits, is widely reported to be 2–2.5%. However, DP has been diagnosed in different ways across studies, resulting in differing prevalence rates. In the current investigation, we estimated the range of DP prevalence by administering well-validated objective and subjective face recognition measures to an unselected web-based sample of 3116 18-55 year-olds and applying DP diagnostic cutoffs from the last 14 years. We found estimated prevalence rates ranged from .64–5.42% when using a z-score approach and .13–2.95% when using a percentile approach, with the most commonly used cutoffs by researchers having a prevalence rate of .93% (z-score, .45% when using percentiles). We next used multiple cluster analyses to examine whether there was a natural grouping of poorer face recognizers but failed to find consistent grouping beyond those with generally above versus below average face recognition. Lastly, we investigated whether DP studies with more relaxed diagnostic cutoffs were associated with better performance on the Cambridge Face Perception Test. In a sample of 43 studies, there was a weak nonsignificant association between greater diagnostic strictness and better DP face perception accuracy (Kendall's tau-b correlation, τb =.18 z-score; τb = .11 percentiles). Together, these results suggest that researchers have used more conservative DP diagnostic cutoffs than the widely reported 2–2.5% prevalence. We discuss the strengths and weaknesses of using more inclusive cutoffs, such as identifying mild and major forms of DP based on DSM-5.